DETERMINANTS OF OCCUPATIONAL STRESS ON TAPPERS WORKERS IN BULUKUMBA REGENCY - Nurwahidah, Nurwahidah; Nildawati, Nildawati; Ekasari, Ranti (HEARTY, 2024)
Occupational stress is a global issue that is influenced by occupational, individual, organizational and psychosocial factors. Excessive workload and pressure can trigger occupational stress. This study was conducted with the aim of knowing the factors associated with work stress in tappers workers at PT PP London Sumatra Indonesia Tbk in Tamatto Village, Ujung Loe District, Bulukumba Regency. This research is a quantitative research with cross sectional study design. Data analysis used is univariate analysis with frequency distribution and bivariate analysis with chi-square test. The number of samples in this study were 200 workers obtained using accidental sampling technique. Factors that affect job stress in tappers are organizational factors, namely, temperature physical environment, career development and workload. The results showed that there was a significant relationship, namely the physical environment of temperature (p-value = 0.002), career development (p-value = 0.000) and workload (p-value = 0.000) to work stress on tappers workers at PT PP London Sumatra Indonesia Tbk while other variables showed an insignificant relationship between age (p-value = 0, 618), married status (p-value=0.614), last education (p-value=0.573), length of service (p-value=0.982) to work stress on tappers workers at PT PP London Sumatra Indonesia Tbk in Tamatto Village, Ujung Loe District, Bulukumba Regency.